H. Pylori Infection Prevalence at the Digestive Endoscopy - Rubina Shah, Tariq Tahir Butt, Muhammad Sohaib Ejaz Khan, Muhammad Azam, Mohammad Saud Salem Numan, Ayesha Shafique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The diagnosis of the oeso-gastroduodenal diseases has been revolutionized by the advances in in endoscopy especially gastroscopy. But there is limited data about the digestive endoscopy techniques is available. Objective: The study was carried out to analyze the endoscopic lesions profile and occurrence of H.pylori at the time of endoscopy (digestive). Study design: It is a retrospective study conducted at medicine department of Sialkot Medical College, Sialkot from June 2021 to December 2021. Material and Methods: There were 121 patients that participated in this study and among them there were 58 male and 63 female members. The patients were aware of the objective and signed the consent willingly. All the patients went through gastrointestinal endoscopy and their data was collected for analysis. The review board and ethical committee of our institute teaching hospital approved the study. According to the inclusion criteria the patients that underwent the gastrointestinal endoscopy were included in this research. Results: The data suggest that there were more female members that consulted doctor related to this issue as compared to men. It was also observed that there were more patients under 50 age who came to get their treatment done as compared to older patients. Data showed that the common sign and symptom that was reported by the patients was epigastralgia with 82% patients reporting it. Then the second most dominant symptom was vomiting followed by gastrointestinal bleeding and loss of weight. There were many patients that reported multiple of these symptoms at the same time. . It was observed that the data of esophageal varices was found to be linked with male sex with a significant p value of 0.047. The gastritis linked to H.pylori was associated with lesion. Conclusion: The goal of the study was to find the profile of endoscopic lesions and H.pylori prevalence, its infection in patients undergoing digestive endoscopy. The study was retrospective, and analysis was carried out to find the different types of endoscopic lesions and their impact on certain demographic parameters. The gastric tumor was found to be correlated with age, tobacco had some impact on peptic ulcer occurrence. And the upper gastrointestinal endoscopy was commonly observed in majority of the patients. Keywords: endoscopic lesions, H.pylori, and gastric tumor